Fast Track Legislation from the Perspective of People's Sovereignty: Criticism of the Weakening of Public Participation in the Legislative Process - Kusnadi Umar (JOSH: Journal of Sharia, 2026)
This article examines the practice of fast-track legislation in the formation of laws in Indonesia from the perspective of popular sovereignty and democratic constitutionalism. This study aims to analyze how accelerated legislation affects the quality of public participation in lawmaking. This study uses a normative legal research method with a legislative, conceptual, and constitutional approach. A literature review was used to collect primary, secondary, and tertiary legal materials. The results of the study show that the fast-track legislation mechanism has led to technocratic legislative practices characterized by difficulty in accessing supporting documents (academic papers and draft bills) and limited space for deliberation, causing the substantive legitimacy of laws to be increasingly eroded. Strengthening participation through amendments to Article 96 of Law No. 12 of 2011 through Law No. 13 of 2022 by adopting the concept of meaningful participation as formulated by the Constitutional Court in Decision No. 91/PUU-XVIII/2020 has proven unable to minimize the impact of fast-track legislation. -track legislation. This article concludes that the constitutional limits of fast-track legislation lie in the fulfillment of public legitimacy, which can only be achieved through meaningful participation. Therefore, strict regulations regarding time limits for the formation of laws and meaningful participation mechanisms are necessary to prevent tokenistic legislation that contradicts the principle of people's sovereignty.